Ритм и смысл стихотворения Пушкина «Буря» [Pushkin’s “Buria”: The Meaning of Rhythm] - Dotsenko, Sergei (Slavica Revalensia, 2021)
This article addresses the meaning of the verse form of Alexander Pushkin’s poem “Buria” (1825). The poem’s monotonous rhythm corresponds to the theme of waves hitting the seashore and the rock in the same monotonous manner. The rhythmic structure of the poem implies that it can be divided into four three-line sections, each of which alternates between two rhythmic forms of iambic tetrameter (IV—IV—I, IV—IV—I, etc.). The stanzaic structure of the poem, which is a monostrophe, helps one to sense that pattern.